Understanding Resilience Among Undergraduate Nursing Students: Dimensions and Associated Factors - Maria Cristina Queiroz Vaz Pereira; Carolina Miguel da Graça Henriques; Amélia Maria da Fonseca Simões Figueiredo; Ana Lúcia da Silva João (Nursing Reports, 2026)
Background: Resilience is an important resource in nursing education, supporting students in adapting to demanding academic and clinical environments. However, evidence regarding the factors associated with resilience among nursing students remains inconsistent. This study aimed to examine the factors associated with resilience among undergraduate nursing students, with particular emphasis on gender, age, academic progression, institutional context, and selected sociodemographic characteristics. Methods: A cross-sectional quantitative study was conducted with 263 undergraduate nursing students from two higher education institutions in Portugal. Data were collected using the Takviriyanun Resilience Factors Scale, adapted and validated for the Portuguese population. Descriptive and inferential statistical analyses were performed to examine the two dimensions of the scale—Personal and Social Support Skills and Problem-Solving Skills—and their associations with sociodemographic and academic variables. Results: Students reported generally favourable levels of resilience-related factors, with higher scores observed in items reflecting personal responsibility and perceived social support. Comparatively lower scores were observed for items related to calmness and patience, confidence, optimism, and perceived social acceptance. A statistically significant gender difference was found in Problem-Solving Skills, with male students showing higher mean ranks than female students (p = 0.038); however, the effect size was small (r = 0.13). A moderate positive correlation was observed between Problem-Solving Skills and Personal and Social Support Skills (ρ = 0.394, p < 0.001). No statistically significant associations were found between the resilience dimensions and age, year of study, higher education institution, displacement status, place of residence, or religious affiliation. Conclusions: Undergraduate nursing students demonstrated generally favourable levels of resilience-related factors. Personal and Social Support Skills and Problem-Solving Skills were positively associated, suggesting a meaningful relationship between interpersonal resources and problem-solving competencies. Although a small gender difference was observed in Problem-Solving Skills, the findings do not indicate substantial gender-related differences in resilience-related factors. Educational strategies aimed at strengthening problem-solving, adaptive coping, emotional self-regulation, and social support may be relevant throughout undergraduate nursing education. Longitudinal and multicentre studies are warranted to further investigate the factors associated with resilience and to evaluate the effectiveness of resilience-focused educational interventions.